The image of historical figures in kazakh literature - Kussainova, Meiramgul; Abdigapbarova (Абдигапбарова), Zhanar (Жанар) (International Journal of Social Science and Humanity vol. 6, no. 6, pp. 437-445, 2016, 2016)
Kazakh literature is rich for writers who wrote fiction about the famous historical figures. Each year, besides legends and folk tales which survived until nowadays a lot of fiction works are written. One of such world-famous historical legends is the legend about Chingis Khan and his descendant – the last khan of Kazakh nation – Kenessary Khan. This paper offers a close analysis of the representation of Chinggis Khan in the Tarikhnama in unpublished dastan composed by the turn of the century Kazakh writer Shadi Zhangiruly. The image of Kenesary Kasimov has been particularly highlighted in the second part of the paper. Kenesary Kasimov who had roots from the dynasty of Chingizidy was the last khan in the Kazakh steppe and the leader of the national liberation movement in the epic poem Nysambai zhirau "Kenesary - Nauryzbai".
Keywords: historical figures; kazakh literature; legends; zhirau